Credit Ratings and Fiscal Responsibility - Hanusch, Marek; Vaaler, Paul (2015)
The authors build on the findings from an earlier analysis, adding to the evidence base for the notion that credit rating agencies contribute to fiscal sustainability. To do so, the authors focus on election periods when political pressures for fiscal expansions are heightened. The literature on political budget cycles documents the tendency for budget deficits to increase in election years as governments attempt to appear economically competent by strategically providing additional publicly financed goods or services, or by cutting taxes. A rating downgrade, however, signals the opposite of competence as it implies an increase in the probability of sovereign default. Since credit ratings are widely observed - by financial markets as well as voters - they in effect serve as a disciplining device for fiscal policy not to submit to short-term spending pressures, thus keeping it responsible. The authors find that: (1) governments going into an election year immediately after a rating downgrade are 27 percentage points more likely to lose at the polls; and (2) governments going into an election year with a negative rating outlook (indicating a higher likelihood of a near-term downgrade) run smaller budget deficits compared to cases with positive or stable outlooks. Ratings act like fiscal rules disciplining governments when they are more vulnerable to political pressures on the budget - as opposed to fiscal policies supporting longer-term economic growth and development objectives.